BUCCAL MUCOSAL GRAFT ONLAY TECHNIQUE FOR UPPER URETERIC AND UPJ STRICTURES - Nerli, Rajendra; Rai, Shreyas; Jogula, Abhinay; Patel, Keyur; Bokare, Ashwin (Indonesian Journal of Urology, 2024)
Objective: In this paper we report our experience in the use of buccal mucosal grafts in the reconstruction of difficult upper ureteric and uretero-pelvic junction strictures. Material & Methods: We retrospectively looked at our hospital inpatient and outpatient records of all patients who underwent surgical treatment for benign upper ureteric strictures and ureteropelvic junction strictures. Results: During the study period a total of 22 patients with a mean age of 326.07 years underwent buccal mucosal graft repair. The mean length of the narrowing/stricture was 6.40 1.44 cm. Conclusion: Buccal mucosal onlay graft ureteroplasty is a suitable treatment option for long, complicated benign upper ureteric and select ureteropelvic junction strictures. It is technically simple and capable of providing optimum patency of ureter with good urinary drainage. It is safe and effective. Keywords: Buccal mucosa, ureteric stricture, ureteropelvic junction stricture, graft, ureteroplasty